A hybrid thermal management system for lithium ion batteries combining phase change materials with forced-air cooling. (15th June 2015) - Ling, Ziye; Wang, Fangxian; Fang, Xiaoming; Gao, Xuenong; Zhang, Zhengguo
Highlights: Heat accumulation in PCM causes failures of passive thermal management systems. The introduction of forced air convection improves the reliability of PCMs. Temperature distribution in the hybrid system remains uniform. Active cooling and PCMs play separate roles in battery thermal management. Numerical results agree with experiment data and give theoretic insights. Abstract: Passive thermal management systems using phase change materials (PCMs) provides an effective solution to the overheating of lithium ion batteries. But this study shows heat accumulation in PCMs caused by the inefficient cooling of air natural convection leads to thermal management system failures: The temperature in a battery pack operating continuously outranges the safety limit of 60 °C after two cycles with discharge rate of 1.5 C and 2 C. Here a hybrid system that integrates PCMs with forced air convection is presented. This combined system successfully prevents heat accumulation and maintains the maximum temperature under 50 °C in all cycles. Study on airspeed effects reveals that thermo-physical properties of PCMs dictate the maximum temperature rise and temperature uniformity in the battery pack, while forced air convection plays a critical role in recovering thermal energy storage capacity of PCMs. A numerical study is also carried out and validated with experiment data, which gives theoretic insights on thermo-physical changes in this hybrid battery thermal management system.